Return on Assets and Covid-19: Do Capital Adequacy Ratio, Loan to Deposit Ratio and Operational Efficiency Ratio Matters? - Hendra Sanjaya Kusno; Ony Artauli Simatupang; Tito IM. Rahman Hakim; Ramli Ramli (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2022)
This study aims to test the effect of Capital Adequacy Ratio (CAR), Loan to Deposit (LDR), and Operational Efficiency Ratio (OER) on Return on Assets (ROA) during the Covid-19 pandemic. This study utilizes a purposive sampling method using a population of National Private Commercial Banks (NPCB) for foreign exchange listed on the Indonesia Stock Exchange (IDX). The data used is the Annual Report for the 2019-2020 period which has been published and based on the purposive sampling method the number of samples used is 44. The analytical technique used in this study is multiple linear regression using SPSS 24. Based on the results of the study, it shows that CAR has a significant positive effect on ROA, LDR has no significant effect on ROA, and OER has a negative effect on Return on Assets (ROA).